The Influence of Nitrogen on the Biological Properties of Soil Contaminated with Zinc - Strachel, Rafał (Bull Environ Contam Toxicol, 2016)
This study analyzed the relationship between nitrogen fertilization and the biological properties of soil contaminated with zinc. The influence of various concentrations of zinc and nitrogen on the microbiological and biochemical activity of soil was investigated. In a laboratory experiment, loamy sand with pH(KCl) 5.6 was contaminated with zinc (ZnCl(2)) and fertilized with urea as a source of nitrogen. The activity of acid phosphatase, alkaline phosphatase, urease and β-glucosidase, and microbial counts were determined in soil samples after 2 and 20 weeks of incubation. Zinc generally stimulated hydrolase activity, but the highest zinc dose (1250 mg kg(−1)) led to the inhibition of hydrolases. Nitrogen was not highly effective in neutralizing zinc’s negative effect on enzyme activity, but it stimulated the growth of soil-dwelling microorganisms. The changes in soil acidity observed after the addition of urea modified the structure of microbial communities.